2011
DOI: 10.1021/ja206138d
|View full text |Cite
|
Sign up to set email alerts
|

Total Synthesis of (±)-Cortistatin J from Furan

Abstract: A concise, diastereoselective total synthesis of (±)-cortistatin J has been completed in 20 steps from furan. Key steps include an intramolecular [4 + 3] cyclization of a disubstituted furan with a (Z)-2-(trialkylsilyloxy)-2-enal to construct the tetracyclic core and a (Z)-vinylsilane/iminium ion cyclization to form the A ring.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(20 citation statements)
references
References 45 publications
0
20
0
Order By: Relevance
“…To date, total syntheses have been reported from the Baran, xi Nicolaou, xii Shair, xiii Myers, xiv Hirama, xv and Funk groups, xvi and formal syntheses have been achieved by the Sarpong xvii and Yang groups. xviii Numerous synthetic studies toward the steroidal core of the cortistatins have been published.…”
Section: Introductionmentioning
confidence: 99%
“…To date, total syntheses have been reported from the Baran, xi Nicolaou, xii Shair, xiii Myers, xiv Hirama, xv and Funk groups, xvi and formal syntheses have been achieved by the Sarpong xvii and Yang groups. xviii Numerous synthetic studies toward the steroidal core of the cortistatins have been published.…”
Section: Introductionmentioning
confidence: 99%
“…[42][43][44][45][46][47][48][49][50] We also reported the synthetic study of 24, in which the 7-endo-selective intramolecular Heck reaction and oxy-Michael reaction were used for elaborating the B-ring core structure of 24. [51][52][53] On the other hand, only small quantities of the final compound could be obtained in most cases because the many reaction steps were needed for the total synthesis.…”
Section: Cortistatins From the Marine Spongementioning
confidence: 99%
“…In addition, four formal syntheses, as well as many synthetic studies, have also been reported 5. 6 The oxygen‐bridged ring B, the nucleus of all cortistatins, has been assembled by a range of methods,4–6 including cycloisomerizations, ring‐closing metatheses, ring expansions, cyclizations by radical, alkylation, cross‐coupling, Michael and aldol reactions, as well as cycloadditions, many of which involve the furan nucleus 4h. 5d, 6fh Following our first work on a partial structure,6k herein we report the asymmetric formal total synthesis of cortistatins A ( 1 ) and J ( 2 ), intercepting advanced intermediates in the Nicolaou–Chen total synthesis4cd and the Yamashita–Hirama total synthesis 4g.…”
Section: Desymmetrizing Reduction Of 4[a]mentioning
confidence: 99%